THE CHROME-TANNED GOAT LEATHER FOR HIGH QUALITY OF BATIK - Pancapalaga, W.; Bintoro, V. P.; Pramono, Y. B.; Triatmojo, S. (Diponegoro University, 2014)
in which the first stage aimed to evaluate sodium silica as batik wax releasing agent on chrome leather.Completely randomized design (CRD) was applied in this study. The concentration of sodium silica wastreated as treatments, in which Tl = 0, T2 = 2 g/L, T3: 4 g/L and T4 = 6 g/L. The second stage of thestudy was aimed to evaluate the type of dye used in batik method dyeing on chrome-tanned goat leather.CRD was used and the treatments were types of dye, i.e. T'1 = acid, T'2= indigosol, T'3 = napthol, T'4 =remazol. In both studies, 9 replicates were applied for each treatment. The use of sodium silicateconcentration of 2 g/L resulted in the percentage of release wax of 91.4% and did not degrade the qualityof chrome leather. The type of acid dyes and naphthol provided the best adhesion and color brightnessand resistance to washing treatment, water, sweat, bend, and rub at 4/5 to 5 on a scale of gray. Inconclusion, chrome tanned goat leather with batik dyeing method was recommended to become one ofthe raw materials of leather goods.